Analisis Pembelajaran Tematik Berbasis Kecerdasan Linguistik Siswa Sekolah Dasar di Era Digital - Zul Azmi; Habibah Siregar (Universitas Negeri Makassar, 2022)
This study aims to describe thematic learning based on linguistic intelligence in the digital era. The research method used is descriptive qualitative research method, with pre-field, field, and data analysis steps. Sources of data are sixth grade teachers and all sixth grade students of SDN 007 Tambusai, totaling 24 students consisting of 12 male students and 12 female students. Data collection techniques used are documentation, observation, and interviews. The research instruments used were teacher observation sheets, student observation sheets, and interview guidelines. The data analysis technique was carried out by qualitative data analysis techniques. The results showed that thematic learning based on students' linguistic intelligence was in the high category. The linguistic intelligence of male students is lower than the linguistic intelligence of female students. The conclusion of this research is that thematic learning based on students' linguistic intelligence is classified as high because teachers who implement thematic learning in elementary schools actually implement thematic learning very well. Further research is needed on the application of other intelligence - based thematic learning.